Preparation and performance evaluation of an innovative pervious concrete pavement. (1st May 2017) - Li, Jiusu; Zhang, Yi; Liu, Guanlan; Peng, Xinghai
Highlights: High strength pervious concrete pavement based on reactive powder concrete. Solution of low strength, high likelihood clogging and inconvenient maintenance. Characteristics of high compressive strength and favorable permeability. Combination of efficient drainage and clogging-preventing in precast concrete pavement system. Abstract: The low strength, high likelihood for clogging and inconvenient maintenance are three main challenges for the wider application of pervious concrete pavement. To overcome these challenges, a high strength pervious concrete (HSPC) pavement was designed and prepared by introducing reactive powder concrete (RPC) as the matrix in addition to constructing accessible pores. Optimized mix proportion of RPC and the porosity were also evaluated in the design and preparation stage. After successful production of HSPC, its performance (e.g. compressive strength, permeability) was evaluated via multiple mechanical and physical tests. As for the experimental results for HSPC, its 7 days compressive strength peaked at 61.37 MPa together with a 13.02 mm/s corresponding permeability coefficient, which indicates a favorable performance for wide application. In addition, referring to current technologies of prefabricated concrete pavement, (e.g., Miller super-slab system, Michigan system), a tongue-and-groove connecting structure was designed and fabricated in the pervious concrete. Finally, a drainage system was designed to exclude the clogging dusts in the pores of the HSPC pavement efficiently, where the clogging dusts were excluded from bottom to top. This innovative high strength pervious concrete has the potential to allow of a wider application of this material.